2023
DOI: 10.1136/jitc-2022-005813
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human phase Ib trial of M9241 (NHS-IL12) plus avelumab in patients with advanced solid tumors, including dose expansion in patients with advanced urothelial carcinoma

Abstract: BackgroundIn preclinical studies, combining M9241 (a novel immunocytokine containing interleukin (IL)-12 heterodimers) with avelumab (anti-programmed death ligand 1 antibody) resulted in additive or synergistic antitumor effects. We report dose-escalation and dose-expansion results from the phase Ib JAVELIN IL-12 trial investigating M9241 plus avelumab.MethodsIn the dose-escalation part of JAVELIN IL-12 (NCT02994953), eligible patients had locally advanced or metastatic solid tumors; in the dose-expansion part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In a phase 1b study (NCT02994953), patients with locally advanced or metastatic solid tumors treated with NHS-IL12 and avelumab experienced clinical responses, with some patients achieving prolonged clinical benefit; notably two patients with advanced bladder cancer experienced prolonged complete responses. The safety profile was similar to that observed with individual agents (58).…”
Section: Nhs-il12 In Combination Therapysupporting
confidence: 74%
See 2 more Smart Citations
“…In a phase 1b study (NCT02994953), patients with locally advanced or metastatic solid tumors treated with NHS-IL12 and avelumab experienced clinical responses, with some patients achieving prolonged clinical benefit; notably two patients with advanced bladder cancer experienced prolonged complete responses. The safety profile was similar to that observed with individual agents (58).…”
Section: Nhs-il12 In Combination Therapysupporting
confidence: 74%
“…Multiple preclinical and clinical studies have demonstrated the tumor suppressive ability of NHS-IL12 as a single agent ( 22 , 35 37 , 56 ). Mounting preclinical and clinical evidence supports the use of NHS-IL12 as an integral component of combination therapies for the treatment of solid cancers, including in combination with immune checkpoint blockade and other treatment modalities ( 35 , 40 , 43 , 45 , 46 , 52 , 53 , 58 , 60 , 61 ). A unique aspect of NHS-IL12 versus rIL-12 is its ability to localize to the tumor, thereby eliciting local IFNγ production via activation, maturation, and expansion of NK and CD8 + TILs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was not the case for VLV-IL-17ECD and VLV-shRNA PDL-1 (data not shown). Although treatment with IL-12 alone represents an ideal approach for tumor immunotherapy due to its ability to activate cytotoxic T lymphocytes (39-45), it had modest effects in clinical trials (46,47). Indeed, when we compared the immunological changes induced by CARG-2020 and VLV-IL12, we observed major differences in the regulation of M1/M2 macrophages and MDSCs.…”
Section: Resultsmentioning
confidence: 99%
“…The MTD of NHS-IL12 was determined to be 16.8 μg/kg, which is much higher than the MTD for rIL-12 of 0.5 to 1 μg/kg, suggesting the possibility of steric hindrance of the cytokine portion of NHS-IL12. Note that NHS-IL12 was originally administered every 4 weeks as monotherapy and is currently being developed in combination with a checkpoint inhibitor given every 2 weeks ( 40 ).…”
Section: Discussionmentioning
confidence: 99%